2015
DOI: 10.1111/phpp.12170
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinomas on sun‐protected vs. sun‐exposed body sites: a comparison of phenotypic and environmental risk factors

Abstract: BCCs on sun-protected sites arise as a result of excessive sun exposure, most likely combined with phenotypic susceptibility. The strong negative association with nevi also suggests that there are constitutional factors that underlie the propensity for BCCs to arise on these body sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
1
9
0
1
Order By: Relevance
“…Nevi have an uncertain relationship with heavy sun damage . The body site associations of adult nevi with BCC on the head and neck, but not the trunk, and any solar keratoses with BCC on all body sites support similar Queensland findings . Childhood freckling too was a risk factor at all body sites.…”
Section: Discussionsupporting
confidence: 58%
“…Nevi have an uncertain relationship with heavy sun damage . The body site associations of adult nevi with BCC on the head and neck, but not the trunk, and any solar keratoses with BCC on all body sites support similar Queensland findings . Childhood freckling too was a risk factor at all body sites.…”
Section: Discussionsupporting
confidence: 58%
“…This study was nested within the Queensland BCC Study (QBS), carried out in Brisbane, Queensland, Australia. The QBS aimed to compare the phenotypic characteristics and environmental risk factors in people who were newly diagnosed with BCC arising on anatomic sites that are usually protected by clothing with those of people newly diagnosed with BCC on anatomic sites that are habitually exposed.…”
Section: Methodsmentioning
confidence: 99%
“…Truncal BCCs are predominantly of the superficial subtype, whereas BCCs on the head and neck are most commonly nodular . Thus, there are suggestions that the pathophysiology of BCCs arising on different anatomic sites and developing into different histological subtypes differs …”
Section: Introductionmentioning
confidence: 99%
“…[16] Since this body part represents the primary area of permanently sun-exposed skin in humans, this reinforces cumulative sun exposure as the main risk factor for BCC. However, the fact that about one-quarter of BCC lesions occur on anatomical sites that are not habitually exposed to the sun, such as the trunk, [18] indicates that discontinuous episodes of intense sunlight exposure may also play an important role in tumor pathogenesis. Epidemiological studies [19,20] have confirmed such a hypothesis and found that intermittent solar exposure (including severe sunburns, especially in childhood), rather than chronic exposure, was a more prejudicial etiological determinant in BCC carcinogenesis.…”
Section: A Ultraviolet Radiation Exposurementioning
confidence: 99%